Hematological and incubation parameters of chicks from young breeders eggs: Variation with sex and incubation temperature - Morita, Viviane de Souza [UNESP]; Boleli, Isabel Cristina [UNESP]; Oliveira, João Ademir de [UNESP] (My University, 2010)
This experiment analyzed the effect of sex and incubation temperature on daily mass loss and eggshell conductance, embryo mortality rates, incubation duration, hematological parameters and body, liver, heart and bursa weights of neonatal chicks from young breeders. The daily mass loss was higher at incubation temperature of 39°C. The eggshell conductance rate increased with the temperature. The total and partial duration of incubation were lower for eggs incubated at 39°C. The time taken by the chick to leave the eggshell did not differ below and above the thermoneutral temperature. The total and intermediate embryo mortality rates increased with the incubation temperature, whereas the early and late embryo mortality rates were higher at incubation temperature of 39°C. Sex did not influence the analyzed parameters, while the incubation temperature did not affect the body and bursa weight and the erythrocytes characteristics. The liver weight of chicks incubated at 36°C was higher than the incubated at 39°C, however there were no differences among the liver weight from chicks incubated at 36 and 39°C and those incubated at 37.5°C. The number of heterophils and the heterophil/lymphocyte ratio (H/L ratio) increased following the temperature, whereas the number of lymphocytes decreased at high temperatures. The other leukocyte parameters did not suffer influence of temperature. Males and females presented similar response to variation of incubation temperatures (36, 37.5 and 39°C) and demonstrated higher sensibility to temperatures above the thermoneutral. Moreover, temperatures below the thermoneutral demonstrated to be better for improvement of hatchability and development of chicks from light eggs. © Asian Network for Scientific Information, 2010.
Keywords: Chick; Erythrogram; Leukogram; Thermal stress